KOALISI MASYARAKAT LOKAL PRIBUMI GUGAT AMNT : ANALISIS WACANA KRITIS - Haryanti, Eka (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
Every choice of meaning is ideologically motivated. Ideology is most effective when the work is not visible. Interpreting ideology in the text can be seen from the choice of vocabulary and grammatical construction. To analyze it we need to interpret not only the text but also the relationship between the text, and its social conditions. According to Fairclough, they can be grouped into three stages, namely description, interpretation and explanation. Stages of description relate to the formal nature of texts, interpretations relating to the relationship between texts and their interactions, explanations relating to the relationship between interpretations and social context.To analyze data using referential methods, substitution methods and abductive inference methods. The referential method is to analyze the system of assessment and discourse intertextuality of texts. To carry out an analysis of a valid grading system a substitution method is needed. Then the abductive inference method is needed to analyze the relationship between texts.From the results of data analysis, it can be concluded that each media has its own way of expressing its ideology. Ideology has closed the relationship with the target market that is the reader. Rungan Samawa is an online place for Sumbawa people, the news is very clear and concise, with a sharp choice of vocabulary, all related to the genre of news they have. The Case of the Local Indigenous Community Coalition Sued Amnt is a form of concern for the Samawa people who are all over the world.